PERUVIAN MILLENIALS: FEATURES AND PROJECTIONS OF LIFE - Begazo Villanueva, José Domingo (2015)
This paper addresses the issue of the Millennials Generation or Generation Y, comprising those born between 1981 and 2000. This generation has revolutionized and changed the habits of the consumer society compared to other generations, changing market strategies of large corporations especially in its potential brand also called Branding. Currently, this generation is between 16 and 35 years, according CEPLAN Peru in the next 10 or 15 years the PEA of Peru will be charged mainly by people belonging to the group of so-called Millennials, as they will be around 7 million people; Another important fact is that by 2025 to 2030, over 60% of the labor force will consist of digital natives; ie by millennials and post millennials. Peruvian Millennials are big fans of technology, and one of its symbols, even greater than the laptop or TV, is their Smartphone. They use it to surf the internet, the better-off making purchases online and generate content on their social networks, etc. They are always willing to share their experiences, what has not shared has no value and never has existed. The concept of Millennials in Peru is linked to millennials Europe and the United States, Human Resource consultant Ronald ER conducted an investigation which established the similarity of the Western millennials with classes A, B and C Peruvian high. Following this paper we propose strategies of value to be used by organizations having as view an universe led by Millennials.